Use of a novel helical tack system for the management of challenging upper gastrointestinal defects - Prashanth Rau, MD; Mark Hanscom, MD; Dhruval Amin, MD; Arslan Talat, MD; Anwar Dudekala, MD; Jaroslav Zivny, MD; Christopher Marshall, MD; Neil B. Marya, MD (VideoGIE, 2022)
Background and Aims: Increasingly, gastroenterologists are being asked to assist in the closure of defects. Although there are several available tools that can be used for defect closure, there remains a need for devices that are easy to use, effective, and durable. The aim of this case series is to demonstrate the use of a novel helical tack system in the closure of upper GI defects. Methods: Two cases of challenging upper GI defects were identified. One case involved a perforated duodenal ulcer, and the other involved a nonhealing marginal ulcer. In both cases, the helical tack system was used for defect closure. Results: In both cases, defect closure was achieved using the helical tack system; however, 2 series of tacks were required in each case. There were no adverse events. Neither patient has required additional surgical or endoscopic interventions. Conclusions: The helical tack system is a new device that may be useful for the closure of challenging upper GI defects. Additional comparative studies are needed to better understand the advantages and disadvantages of this system relative to other closure tools.